Relações Brasil-EUA no Segundo Governo Vargas : a construção de um imaginário político nas páginas do jornal Última Hora - Damasceno, Natália Abreu (2016)
Thirty-first of March of 1964. The coup movement that initiated in Brazil a regime of dictatorial character was under way. The military government took on the task of implanting a complex and bureaucratic machine, under the guise of censorship, violence and propaganda. Newspapers were invaded, artists were deported, art works were banned. In the face of truculence and repression, periodicals emerged that, following an international trend, adopted a countercultural bias in their publications, moving in the direction of the New Left and later being called the alternative press. Such vehicles, such as the tabloid O Pasquim, used unconventional language to the media, abusing the use of images and good humor that, in a short time, began to subvert the most expensive values to the military regime. In view of this panorama, this research aims to use the cartoon as a historiographic source, in order to evidence the use of humor as a possible tool of resistance to oppression faced by the military after the 1964 coup. For this, uses the cartoons published by Ziraldo In the newspaper O Pasquim between the years of 1969 and 1974, period that includes the Medici government and the denominated Years of Lead. The research seeks to raise the metaphors and figures of language that, through illustration, deceived the censorship and the organs of information that worked in the service of the regime. In addition, it intends to demonstrate the constitution of a cultural resistance, going through the path of heterodox Marxism and the propositions of the Italian Antonio Gramsci. In order to understand the effects of meaning produced by the images and how they (un) stabilized military ideas, the study seeks contributions from the French discourse analysis, establishing a relationship between history and history, in order to Cartoons were constituted, or not, as a vehicle of resistance to the threat forged by the dictatorial regime? This work denoted that what had not been said, that is, verbalized as a result of censorship and repression, may have become latent in the illustrations, together with other sources, came to constitute an important vestige of the history of resistance in the Brazil during the military government